Making the case for prophylactic use of betaine to promote brain health in young (15–24 year old) athletes at risk for concussion - Knight, Leena S.; Knight, Thomas A. (Frontiers in Neuroscience, 2023)
Betaine supplementation in the context of human nutrition, athletic performance, and clinical therapy demonstrate that the osmolyte and methyl donor, betaine, is cytoprotective and beneficial to human health. These studies also demonstrate that betaine supplementation in humans is straight-forward and report no adverse effects. Here, we explore betaine uptake in the central nervous system (CNS) and contribute to evidence that betaine may be uniquely protective to the brain. We specifically describe the therapeutic potential of betaine and explore the potential implications of betaine on inhibition mediated by GABA and glycine neurotransmission. The influence of betaine on neurophysiology complement betaine’s role as an osmolyte and metabolite and is consistent with clinical evidence of betaine-mediated improvements to cognitive function (reported in elderly populations) and its anti-convulsant properties. Betaine’s therapeutic potential in neurological disorders including epilepsy and neurodegenerative diseases combined with benefits of betaine supplementation on athletic performance support the unique application of betaine as a prophylaxis to concussion. As an example, we identify young athletes (15-24 years old), particular female athletes, for prophylactic betaine supplementation to promote brain health and resilience in a cohort at high-risk for concussion and for developing Alzheimer’s Disease.